SISTEM INFORMASI PERPUSTAKAAN PADA SMP NEGERI 1 PURBA - Yessy Dearni C. Saragih; Rimbun Siringoringo; Rena Nainggolan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Information systems are needed in the library to support knowledge, insight, and information for students and for teachers in schools in supporting the teaching and learning process in schools. This information is data that is processed into a form that is more useful and more meaningful to those who receive it. The design and manufacture of a web-based library information system at SMP Negeri 1 Purba is an element that can influence the operational tasks of the school. Information that is less fast, less accurate, and less efficient can be solved by implementing this system, it is very necessary for libraries to help the performance of data management and transactions that take place in the library. The library is one of the work units in the form of a place to collect, store, manage and organize a collection of library materials systematically to be used by users as a source of information as well as a fun learning tool. The author's goal is to make it easier to borrow books that are done with this system through a computer so that if there is a lack of accuracy that can hinder the smooth activities of the library, it can be overcome